Influence of ocean tides and ice shelves on ocean–ice interactions and dense shelf water formation in the D'Urville Sea, Antarctica. (June 2021) - Huot, Pierre-Vincent; Fichefet, Thierry; Jourdain, Nicolas C.; Mathiot, Pierre; Rousset, Clément; Kittel, Christoph; Fettweis, Xavier
Abstract: The D'Urville Sea, East Antarctica, is a major source of Dense Shelf Water (DSW), a precursor of Antarctic Bottom Water (AABW). AABW is a key water mass involved in the worldwide ocean circulation and long-term climate variability. The properties of AABW in global climate models suffer from several biases, making climate projections uncertain. These models are potentially omitting or misrepresenting important mechanisms involved in the formation of DSW, such as tides and ocean–ice shelf interactions. Recent studies pointed out that tides and ice shelves significantly influence the coastal seas of Antarctica, where AABW originates from. Yet, the implications of these two processes in the formation and evolution of DSW are poorly understood, in particular in the D'Urville Sea. Using a series of NEMO-LIM numerical simulations, we assess the sensitivity of dense water formation in the D'Urville Sea to the representation of tides and ocean–ice shelf interactions during the years 2010–2015. We show that the ice shelves off Adélie Land are highly sensitive to tidal forcing, with a significant basal melt increase in the presence of tides. Ice shelf basal melt freshens and cools the ocean over significant portions of the coastal seas at the depth of the ice shelf draft. An opposite warming and increase in salinity are found in the upper layers. The influence of ice shelf basal melt on the ocean is largely increased in the presence of tides. However, the production of sea ice is found to be mostly unaffected by these two processes. Water mass transport out of polynyas and ice shelf cavities are then investigated, together with their sensitivity to tides and ocean–ice shelf interactions. Ice shelf basal melt impacts the volume of dense waters in two ways: (1) Dense Shelf Water and Modified Shelf Water are consumed to form water masses of intermediate density inside the ice shelf cavities, and (2) the freshening of the ocean subsurface makes its transformation into dense water by sea ice formation more difficult. These results suggest that ice shelf basal melt variability can explain part of the observed changes of dense water properties, and may also affect the production of dense water in a future climate. Highlights: Tidal forcing enhances ice shelf basal melt by more than 60% in the D'Urville Sea. Ice shelf melt cools and freshens the subsurface ocean, and warms the top layers. Ice shelf melt and tides reduce the volume of dense water formed off Adélie Land.